Reduplikacje jako uniwersalium jezykowe - Antoniak, Dorota (Investigationes Linguisticae, 2005)
The aim of this paper is to give a cross linguistic comparative study on reduplication. Different definitions and theories are collected here to show how complex the case of this simple process is. By presenting a wide range of functions it performs in the world languages, it will be shown that reduplication plays an important role in communication and even that it should be seen as part of Universal Grammar.